Multiple minimal choices: ideology and multiple choice English language testing in Thailand / Thomas Hoy - Hoy, Thomas (ACRULeT, Faculty of Education & UiTM Press, 2007)
Thailand’s educational system is plagued by rote learning, deference to authority, and habits of uncritical thinking. One of the culprits is the emphasis on regurgitating “facts” through multiple choice language testing. This paper addresses the ideological responses and habits that multiple choice language tests demand and reinforce. Through an examination of practice questions for vocabulary tests at a major Thai university a number of contentions about multiple choice vocabulary testing are developed. Students need to imagine the examiner’s ideal context for the statement that is tested and they need to anticipate the examiner’s value system and ideology. These tests breed conformism and punish curiosity about the language. The time and energy that students spend in studying for them retards and deforms more important aspects of linguistic performance and also their intellectual growth in general.